Preserving Cultural Values in Shaping the Character of Elementary School Students Through Ondel Ondel Betawi - Yuliyanah Yuliyanah; Wihdatul Ummah; Ayu Widya Fatmawati; Yosi Gumala (Universitas Muhammadiyah Enrekang, 2024)
Indonesia is a country that has many cultures and tribes, one of which is the Betawi tribe, one of their cultures is the giant Betawi doll which is usually called Ondel-Ondel, people consider it a sacred culture and very appropriate to use in ancestor worship ceremonies. spirit. According to a cultural expert, Ondel-Ondel, also called barongan or more recently. very closely related to Betawi culture. Therefore, exploring local wisdom values ​​is a strategic step in an effort to build national character. This research aims to identify various types of local Betawi culture that can be included in elementary school thematic material. Elementary school thematic material in Betawi is the subject of this research, and the context and content of local Betawi culture is the research subject. This research collects data through observation and interviews. The results of the research show that local Ondel-Ondel culture can be integrated into thematic material in elementary schools including (1) traditional rituals, (2) ethnic diversity, and (3) honesty, (4) works of art, (5) cultural sites, (6) have a brave attitude (7) handicrafts The results show that local Betawi culture can be included in thematic material in elementary schools